ISOMERISASI POLIMER MELALUI REAKSI SAIN SAYEF UNTUK MENGUBAH KONFIGURASI HTPB (HYDROXYL TERMINATED POLYBUTADIENE) POLYMER ISOMERIZATION BY SAIN SAYEF REACTION TO MODIFY CONFIGURATION OF HTPB (HYDROXYL TERMINATED POLYBUTADIENE) Heru Budi Wibowo PDF 137- - Wibowo , Heri Budi (BRIN Publishing, 2016)
One of the problems in the synthesis of Hydroxyl Terminated Polybutadiene for propellant binders is the level of vinyl is high (up to 30%), while the desired product is 20%. Vinyl bond can be reduced if the chain can be broken with the addition of a hydroxyl group. The research objective is to reduce the amount of vinyl structure in HTPB with the addition of double bonds in the vinyl by applying Sayef Sain reaction. HTPB is reacted with concentrated hydrogen peroxide with the Sain Sayef catalyst in the 1 liter autoclave reactor with ethanol for 1-3 hours at 100Â° C. After being purified by extraction in hot water and drying, it is analyzed by an infrared spectrometer. The result shows that there is a change in the concentrations of vinyl within the polymers produced by observing the absorption of vinyl groups at a wavelength of 690cm-1. Optimal results obtained with vinyl content of 20% with a temperature of 100Â° C for 90 minutes. In general, the quality of HTPB can be increased by reducing the levels of vinyl which allowing the HTPB composition to have a vinyl content reduced to 19%.